Crisis and Escalation in Cyberspace - Libicki, Martin C. (RAND Corporation, 2012)
The chances are growing that the United States will find itself in a crisis in cyberspace-the escalation of tensions associated with a major cyberattack, suspicions that one has taken place, or fears that it might do so soon. Such crises can be managed by taking steps to reduce the incentives for other states to step in, controlling the narrative, understanding the stability parameters of the crises, and recognizing escalation risks.